Inside Back Cover: Excited‐State Dynamics of Pentacene Derivatives with Stable Radical Substituents (Angew. Chem. Int. Ed. 26/2014). Issue 26 (2nd May 2014) - Ito, Akitaka; Shimizu, Akihiro; Kishida, Noriaki; Kawanaka, Yusuke; Kosumi, Daisuke; Hashimoto, Hideki; Teki, Yoshio
<x xml:space="preserve">Abstract</x> More than one pentacene triplet is produced from the absorption of one photon. In their Communication on page 6715 ff., Y. Teki et al. describe how transient absorption measurements performed on pentacene derivatives with stable radical substituents in dilute solution demonstrate that the ultrafast formation of a triplet excited state in the pentacene moiety (violet) from a photoexcited singlet state (green) occurs through contributions of enhanced intersystem crossing and singlet fission.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>